Health promotion in schools for youth and adult education: an action-research differentiating news Fake News (Revista Contexto & Educação, 2023)
This study aimed to investigate how an action research using news and/or Fake News on health in social networks can mediate and promote scientific education for young people and adults. The target space of the research is a state school in the basic education network, where the teacher-researcher is in charge of the discipline of Biology and carried out the action-research in a completely remote way. The theme arose from the perception of teachers and students who are still experiencing the COVID-19 pandemic. The proposal is structured in seven stages, the last one contemplating the construction of audios on health-related news, were transformed into episodes of a Podcast, corroborating with the initial idea of ​​promoting Health Literacy for students in Youth and Adult Education